Analisis Pengaruh Perilaku Konsumen Dalam Pengambilan Keputusan Pembelian Online Masyarakat Kabupaten Brebes Pada E-Commerce Shoppe - Mohamad Basuni; Roby Setiadi; Gian Fitralisma; Syariefful Ikhwan (STEKOM PRESS, 2023)
Consumer behavior is the basis for consumers to make purchasing decisions. Consumer behavior is an activity that is closely related to the process of purchasing goods or services. In this study, the independent variable is consumer behavior (X), while the dependent variable is online purchasing decisions (Y). This study aims to examine and analyze the influence of consumer behavior in making online purchasing decisions for the people of Brebes Regency on e-commerce shoppe. The type of research used is quantitative research. The processed data is the result of distributing questionnaires to the public or consumers randomly via google form, the number of population is unknown with a sample of 100 respondents who have been processed using SPSS 22. Data analysis techniques used in this study are validity test, reliability test, test normality, simple linear regression test, coefficient of determination test (R²), and t-test (Partial). Based on the t-test (Partial) shows a positive and significant influence on online purchasing decisions with a value of 0.000 <0.05